Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1519/jsc.0b013e31825dd224
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cadence on Cycling Efficiency and Local Tissue Oxygenation

Abstract: The purpose of this study was to compare 3 cycling cadences in efficiency/economy, local tissue oxygen saturation, heart rate, blood lactate, and global and local rating of perceived exertion (RPE). Subjects were 14 trained cyclists/triathletes (mean age 30.1 ± 5.3 years; VO(2) peak 60.2 ± 5.0 ml·kg(-1)·min(-1)) who performed three 8-minute cadence trials (60, 80, and 100 rpm) at 75% of previously measured peak power. Oxygen consumption and respiratory exchange ratio were used to calculate efficiency and econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Similarly, higher cadences may be related to greater instability, which would imply higher needs of muscle activation for postural control and would ultimately lead to higher energy consumption, and therefore, worse efficiency [ 45 ]. When compared to studies in other sports, our findings were in agreement with those of Neilsen et al [ 46 ] and Jacobs et al [ 20 ] in cycling, Gonzalez-Aramendi [ 24 ] in traditional rowing, and Kraaijenbrink et al [ 25 ] in hand cycling, as all of them found that lower cadences were related to better efficiency and economy values. In contrast, Lucia et al [ 21 ] and Mora-Rodriguez and Aguado-Jimenez [ 47 ] in cycling, or Goosey et al [ 26 ] in hand cycling reported that higher cadences were more efficient and economical.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, higher cadences may be related to greater instability, which would imply higher needs of muscle activation for postural control and would ultimately lead to higher energy consumption, and therefore, worse efficiency [ 45 ]. When compared to studies in other sports, our findings were in agreement with those of Neilsen et al [ 46 ] and Jacobs et al [ 20 ] in cycling, Gonzalez-Aramendi [ 24 ] in traditional rowing, and Kraaijenbrink et al [ 25 ] in hand cycling, as all of them found that lower cadences were related to better efficiency and economy values. In contrast, Lucia et al [ 21 ] and Mora-Rodriguez and Aguado-Jimenez [ 47 ] in cycling, or Goosey et al [ 26 ] in hand cycling reported that higher cadences were more efficient and economical.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that this sport takes place in natural environments, with changing wind and waves, the paddling cadence during open sea SUP races may not be constant. Several studies in other sports have suggested that some cadences are more efficient than others [ 6 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In the case of cyclists and triathletes, Jacobs et al [ 20 ] showed how lower cadences were more economical in trained subjects, while de Lucia et al [ 21 ] obtained opposite results with world-class cyclists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have also been performed to determine the optimal pedaling cadence for efficient cycling performance at a given power output. However, no clear consensus has been reached with some studies favoring a low cadence [23] and others a higher cadence [7], also highlighting the different responses observed between elite and recreational cyclists, where elite cyclists specifically train at high cadence [1,26,38]. Increasing cadence when exercising at T vent may affect skeletal muscle oxygenation [15], yet no study to date has explored the effect of altering cadence on TSI when cycling at T vent .…”
Section: Introductionmentioning
confidence: 99%
“…Many laboratory-based studies have sought to determine an optimal cadence (Coast & Welch, 1985 , 90–105 rpm; Eckermann & Millahn, 1967 , 30–60 rpm; Hagberg, Mullin, Giese, & Spitznagel, 1981 , 80–90 rpm; Wildrick, Freedson, & Hamill, 1992 , 35–57 rpm). Little consensus has emerged from these studies with some arguing that high cadences (preferred by professional cyclists) are optimal (Hagberg et al, 1981 ), that optimal cadence varies with work-rate (Foss & Hallen, 2004 ), or that high cadences are not optimal (Jacobs, Berg, Slivka, & Noble, 2013 ; Stebbins, Moore, & Casazza, 2014 ). There is some agreement that very high cadences are inefficient.…”
Section: Introductionmentioning
confidence: 99%